FAKTA-FAKTA PERILAKU MENYIMPANG DALAM MASYARAKAT JEPANG PENDEKATAN SOSIOLOGI SASTRA - Anik Kusyanti, Ni Kadek (Humanis, 2012)
Japan is a modern country that is famous for its manner and cultures. However, In Japanese society also found the fact about deviant behaviors that often happen in Japan. This study use an analysis descriptive method and dialectical method to analyze data. The result showed that in Japanese society often happened some deviant behaviors like Ijime, suicide, self injury, drugs, and smoking. Such behaviors is caused by lack of attention from their parents and a bad environment around them.
Keywords: deviant behaviors, Japanese society